2022
DOI: 10.3390/ijms23105742
|View full text |Cite
|
Sign up to set email alerts
|

Liver Graft Hypothermic Static and Oxygenated Perfusion (HOPE) Strategies: A Mitochondrial Crossroads

Abstract: Marginal liver grafts, such as steatotic livers and those from cardiac death donors, are highly vulnerable to ischemia–reperfusion injury that occurs in the complex route of the graft from “harvest to revascularization”. Recently, several preservation methods have been developed to preserve liver grafts based on hypothermic static preservation and hypothermic oxygenated perfusion (HOPE) strategies, either combined or alone. However, their effects on mitochondrial functions and their relevance have not yet been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…The present research investigates the efficiency of the IGL-2 solution, a modified version of IGL-1, where vasodilatation and antioxidant properties were boosted by increasing five-fold and three-fold the concentration of PEG35 and glutathione, respectively ( Table 1 ). We hypothesized that these boosted properties are the most suitable ones for combining static preservation and dynamic perfusion ([ 32 ], p. 2, [ 33 ]). Moreover, the use of a unique solution for both the static and dynamic preservation solutions could greatly facilitate the logistical hurdles and avoid “interactions” that could be caused by the mixing of the different solutions when static cold storage is combined with HOPE using complete or partial liver grafts, as recently demonstrated by Mabrut et al [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present research investigates the efficiency of the IGL-2 solution, a modified version of IGL-1, where vasodilatation and antioxidant properties were boosted by increasing five-fold and three-fold the concentration of PEG35 and glutathione, respectively ( Table 1 ). We hypothesized that these boosted properties are the most suitable ones for combining static preservation and dynamic perfusion ([ 32 ], p. 2, [ 33 ]). Moreover, the use of a unique solution for both the static and dynamic preservation solutions could greatly facilitate the logistical hurdles and avoid “interactions” that could be caused by the mixing of the different solutions when static cold storage is combined with HOPE using complete or partial liver grafts, as recently demonstrated by Mabrut et al [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 These biomolecules may act as damage-associated molecular patterns (DAMPs) and stimulate multiple signaling pathways and cascades, ultimately leading to cell and organ dysfunction. 17 Therefore, we and others hypothesize that renal injury after liver transplantation may be partly driven by alterations occurring in the liver graft. [4][5][6] We have previously shown that grafts of LT recipients developing early AKI reveal distinct proteomic changes, mainly related to the innate immunity response, inflammation, and ongoing neutrophil degranulation, compared to the liver grafts of patients retaining normal renal function after LT. 6 Given the lack of an obvious effect of HOPE on the development of AKI, we speculate that the altered proteome is not influenced by any of the putative protective mechanisms of HOPE, 17 which seem unable to override the multiple metabolic processes apparently steered from the graft.…”
Section: Discussionmentioning
confidence: 95%
“…17 Therefore, we and others hypothesize that renal injury after liver transplantation may be partly driven by alterations occurring in the liver graft. [4][5][6] We have previously shown that grafts of LT recipients developing early AKI reveal distinct proteomic changes, mainly related to the innate immunity response, inflammation, and ongoing neutrophil degranulation, compared to the liver grafts of patients retaining normal renal function after LT. 6 Given the lack of an obvious effect of HOPE on the development of AKI, we speculate that the altered proteome is not influenced by any of the putative protective mechanisms of HOPE, 17 which seem unable to override the multiple metabolic processes apparently steered from the graft. Most studies using HOPE are performed on ECDs, and a majority report an improvement of the hepatocellular injury and milder transaminase leak in the recipients of HOPE-treated ECD grafts to levels corresponding to standard donors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors suggested that a high expression of UCP2 lowers the bioavailability of ATP and thereby contributes to low outcomes. Consequently, some studies confirmed that low UCP2 expression and/or activity protects the liver against reperfusion injury [ 97 , 98 , 99 , 100 ]. However, other studies correlated a high expression of UCP2 with hepatic protection [ 101 , 102 , 103 ].…”
Section: Uncoupling Proteinsmentioning
confidence: 99%